A MAQASID AL-SYARĪ’AH BASED EVALUATION OF LOCAL GOVERNMENT INTERVENTIONS IN HALAL CERTIFICATION IMPLEMENTATION: EVIDENCE FROM SUMENEP - Khoirun Nasik; Farid Ardyansyah; Ahmad Musadad; Shofiyun Nahidloh; Tri Pujiati; Umi Indasyah Zahro (Universitas Nurul Jadid, 2026)
The expiration of the phased implementation of mandatory halal certification on 17 October 2024 marked a transition from a facilitative to an enforcement-oriented policy phase, creating significant implementation pressures for local governments and micro and small enterprises facing legal, market, and administrative risks. While previous studies have examined halal certification from normative legal and governance perspectives, limited research integrates empirical public policy analysis with a maqasid al-syarī’ah framework to evaluate local government interventions during this post-transition period. Using a qualitative policy analysis approach, this study identifies six local intervention strategies: structured multi-stakeholder coordination; optimization of the self-declare assistance scheme; targeted digital literacy and social media outreach; affirmative programs for remote villages; development of a regional Halal Hub ecosystem; and preventive regulatory socialization for the 2026 mandatory phase. Empirically, 4,053 halal certificates were issued by January 2026, 3,933 through the self-declare scheme, with over 90% of assisted MSMEs completing registration on time. These results indicate that proactive facilitation and adaptive local governance significantly reduced non-compliance risks during the transition. From a maqasid al-syarī’ah perspective, the interventions operationalize multidimensional protection: religion (hifz al-dīn), life (hifz al-nafs), wealth (hifz al-māl), intellect (hifz al-’aql), and lineage (hifz al-nasl). Conceptually, this study proposes a maqasid-based evaluation model linking Islamic normative principles with measurable governance indicators. Theoretically and practically, it positions maqasid as an applied analytical framework and provides evidence-based guidance for adaptive and sustainability-oriented halal governance.